Electrophysiological evidence for the characteristics of implicit self-schema and other-schema in patients with major depressive disorder: An event-related potential study - Yao, Jia-yu; Zheng, Zi-wei; Zhang, Yi; Su, Shan-shan; Wang, Yuan; Tao, Jing; Peng, Yi-hua; Wu, Yan-ru; Jiang, Wen-hui; Qiu, Jian-yin (Frontiers in Psychiatry, 2023)
Background The significance of implicit self-schema and other-schema in major depressive disorder (MDD) is highlighted by both cognitive theory and attachment theory. The purpose of the current study was to investigate the behavioral and event-related potential (ERP) characteristics of implicit schemas in MDD patients. Methods The current study recruited 40 patients with MDD and 33 healthy controls (HCs). The participants were screened for mental disorders using the Mini-International Neuropsychiatric Interview. Hamilton Depression Rating Scale-17 and Hamilton Anxiety Rating Scale-14 were employed to assess the clinical symptoms. Extrinsic Affective Simon Task (EAST) was conducted to measure the characteristics of implicit schemas. Meanwhile, reaction time and electroencephalogram data were recorded. Results Behavioral indexes showed that HCs responded faster to positive self and positive others than negative self (t = −3.304, p = 0.002, Cohen’s d = 0.575) and negative others (t = −3.155, p = 0.003, Cohen’s d = 0.549), respectively. However, MDD did not show this pattern (p > 0.05). The difference in other-EAST effect between HCs and MDD was significant (t = 2.937, p = 0.004, Cohen’s d = 0.691). The ERP indicators of self-schema showed that under the condition of positive self, the mean amplitude of LPP in MDD was significantly smaller than that in HCs (t = −2.180, p = 0.034, Cohen’s d = 0.902). The ERP indexes of other-schema showed that HCs had a larger absolute value of N200 peak amplitude for negative others (t = 2.950, p = 0.005, Cohen’s d = 0.584) and a larger P300 peak amplitude for positive others (t = 2.185, p = 0.033, Cohen’s d = 0.433). The above patterns were not shown in MDD (p > 0.05). The comparison between groups found that under the condition of negative others, the absolute value of N200 peak amplitude in HCs was larger than that in MDD (t = 2.833, p = 0.006, Cohen’s d = 1.404); under the condition of positive others, the P300 peak amplitude (t = −2.906, p = 0.005, Cohen’s d = 1.602) and LPP amplitude (t = −2.367, p = 0.022, Cohen’s d = 1.100) in MDD were smaller than that in HCs. Conclusion Patients with MDD lack positive self-schema and positive other-schema. Implicit other-schema might be related to abnormalities in both the early automatic processing stage and the late elaborate processing stage, while the implicit self-schema might be related only to the abnormality in the late elaborate processing stage.